HOW FOOD CONSUMPTION PATTERN AND DIETARY DIVERSITY INFLUENCE FOOD SECURITY: EVIDENCE FROM DI YOGYAKARTA AND EAST NUSA TENGGARA - Firdaus, Nur; Cahyono, Bintang Dwitya (Jurnal Ekonomi dan Pembangunan, 2017)
Food is an essential need and its role is prominent to human life. In addition, food may have a positive contribution to develop human resources. According to Food Security Agency (Badan Ketahanan Pangan/ BKP), food consumption pattern should meet nutrition standards and follow desirable dietary pattern (Pola Pangan Harapan/ PPH). PPH indicates an overview of food that is consumed by people whether its contains good nutrient or not. This study aims to analyze food consumption pattern and dietary diversity in DI Yogyakarta and East  Nusa Tenggara; and how they influence food security. The household data survey (Susenas) 2014 showed that PPH scores for DI Yogyakarta is higher than East Nusa Tenggara. From these scores, DI Yogyakarta has better food consumption pattern and leads to diverse food; in contrast, food consumption in East Nusa Tenggara has not lead to a healthy pattern. In DI Yogyakarta, people have been diversifying their consumption in accordance with the concept of PPH. This means that people have realized to meet their nutrition by consuming nutritious foods and help them not only to achieve food security but also nutrition security. Moreover, people have used local-based food to be consumed so that they do not depend on their current food. Whilst, in East Nusa Tenggara, people tend to meet their needs regardless their food has good nutrition or not. In addition, dietary diversity or PPH is influenced by some factors, such as education, family size, age of the household head, and expenditure. These results confirm that diverse consumption pattern showed high food security and those factors should be concerned to improve the quality of food consumption.